2015
DOI: 10.1371/journal.pone.0135260
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A Activity Is Necessary for Fission and Fusion of Golgi to Endoplasmic Reticulum Retrograde Tubules

Abstract: It is becoming increasingly accepted that together with vesicles, tubules play a major role in the transfer of cargo between different cellular compartments. In contrast to our understanding of the molecular mechanisms of vesicular transport, little is known about tubular transport. How signal transduction molecules regulate these two modes of membrane transport processes is also poorly understood. In this study we investigated whether protein kinase A (PKA) activity regulates the retrograde, tubular transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…Cells left untreated or treated with 5 μg/ml Brefeldin A (BFA) for 60 min at 37°C were analyzed by immunofluorescence microscopy as described previously [ 47 ]. Fixation of cells with methanol or 4% paraformaldehyde was performed when primary antibody reactivity demanded.…”
Section: Methodsmentioning
confidence: 99%
“…Cells left untreated or treated with 5 μg/ml Brefeldin A (BFA) for 60 min at 37°C were analyzed by immunofluorescence microscopy as described previously [ 47 ]. Fixation of cells with methanol or 4% paraformaldehyde was performed when primary antibody reactivity demanded.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, it has been shown that Golgi-to-ER retrograde transport plays a crucial role in the maintenance of Golgi morphology. Indeed, inhibition of this specific trafficking pathway results in a significant swelling of this organelle [32,[45][46][47][48][49]. To investigate whether the swelling of the Golgi by the inhibition of PSMD14 with CZM could be the result of the inhibition of the Golgi-to-ER retrograde transport, we first validated our findings in HeLa cells.…”
Section: Acute Inhibition Of the Deubiquitinating Enzyme Psmd14 Pertumentioning
confidence: 56%
“…Two other proteins that participates in this retrograde trafficking pathway, such as PKA and UVRAG [32,85], have been shown to be regulated by ubiquitination. Blockers of PKA signaling cause the inhibition of this trafficking pathway, a process that is accompanied by the swelling of the Golgi apparatus [32,49]. It has been shown that the catalytic PKA subunit (PKAc) is ubiquitinated by the CHIP E3 ligase, resulting in proteasomal degradation of PKAc and signaling shutdown [86].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that Golgi-to-ER retrograde transport plays a crucial role in the maintenance of Golgi morphology. Indeed, inhibition of this specific trafficking pathway results in a significant swelling of this organelle 4045 . To investigate whether the swelling of the Golgi by the inhibition of PSMD14 with CZM could be the result of the inhibition of the Golgi-to-ER retrograde transport, we first validated our findings in HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Two other proteins that participates in this retrograde trafficking pathway, such as PKA and UVRAG 44, 76 , have been shown to be regulated by ubiquitination. Blockers of PKA signaling cause inhibition of this trafficking pathway, a process that is accompanied by the swelling of the Golgi apparatus 44, 45 . It has been shown that the catalytic PKA subunit (PKAc) is ubiquitinated by the CHIP E3 ligase, resulting in proteasomal degradation of PKAc and signaling shutdown 77 .…”
Section: Discussionmentioning
confidence: 99%